Biomimetic synthesis of micro/nanostructured tubular TiO2 photocatalyst: adjusting the shape of the outer tube wall from nanoparticles to interlaced nanofibers and nanobelts. Issue 17 (19th April 2017) - Zhang, Guanghui; Zhang, Tianyong; Li, Bin; Zhang, Xia; Hai, Li; Chen, Xingwei; Du, Ping
Abstract : Hierarchical micro/nanostructured tubular TiO2 materials were prepared by an impregnation–calcination method with FCT (the fluff of the chinar tree) as a biological template and titanium tetrachloride (TiCl4 ) as a precursor. Abstract : In this study, hierarchical micro/nanostructured tubular TiO2 photocatalysts were fabricated with the fluff of the chinar tree (FCT) as a biological template and titanium tetrachloride (TiCl4 ) as a precursor through an impregnation–calcination method. The structure, morphology and optical properties were extensively characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), nitrogen adsorption–desorption, Fourier-transform infrared spectroscopy (FTIR), UV-vis diffused reflectance spectroscopy (UV-vis) and photoluminescence (PL) spectra. The results indicated that the FCT played pivotal roles as a template and inducer to assemble the tubular micro/nanostructure. Interestingly, the morphologies and structures of the outer tube wall of the obtained materials could be controlled and tailored by adjusting the dosages of TiCl4 . In addition, the structures of the outer tube wall of the samples could be tuned from cross-linked nanobelts to interlaced nanofibers, and then spherical-likely nanoparticles by adjusting the dosages of TiCl4 . Moreover, the as-prepared TiO2 material exhibited a 99.8% photocatalytic degradation rate for 15 mg L −1 rhodamine B (RhB) in 30 min under a 300 W mercury lamp. Compared with P25, the obtained TiO2 had superior photocatalytic activity. Furthermore, the hierarchical micro/nanostructured tubular TiO2 was easily recycled and had excellent photocatalytic stability.